The Influence of the Human Resource Information System on Employee Performance with Employee Engagement as a Moderating Variable - Trisnawati, Ayu Putri (Jurnal Ilmu Manajemen, 2024)
This study aims to determine and analyze the effect of implementing a human resource information system on employee performance with employee engagement as a moderating variable at an outsourcing company. This research is an explanatory type of research that uses a quantitative approach with a population of 54 internal employees. The sampling technique used is a saturated sample with a sample size of 54 internal employees. The statistical analysis method in this study is Partial Least Square, which is supported by SmartPLS 4.1.0.0 computer software. The result of this study indicates that performance expectancy has a significant effect on employee performance, effort expectancy has a significant effect on employee performance, social influence has no significant effect on employee performance, and facilitating conditions have a substantial impact on employee performance. Employee engagement can’t moderate the relationship between performance expectancy and employee performance; employee engagement can’t moderate the relationship between effort expectancy and employee performance; employee engagement can’t moderate the relationship between social influence and employee performance; employee engagement can’t moderate the relationship between facilitating condition on employee performance. Companies that implement human resource information systems in their work are expected to pay attention to performance expectancy, effort expectancy, and facilitating conditions from human resource information systems because applying them can improve employee performance.